Prioritizing Indecent Image Offenders: A Systematic Review and Economic Approach to Understand the Benefits of Evidence-Based Policing Strategies - Giles, Susan; Alison, Laurence (Frontiers in Psychology, 2021)
CEOP (2013) estimate that there are around 50,000 individuals involved in downloading and sharing indecent images of children (IIOC) in the United Kingdom (UK). This poses challenges for limited police resources. We argue that police officers can make most effective use of limited resources by prioritizing those offenders who pose the greatest risk of contact offending, by nature of demonstrable pedophilia, hebephilia or dual offending status and thus, those at highest risk must be dealt with first. What is currently lacking is a clear idea of the potential scale of the problem in socio-economic terms and why, therefore, it is so important that evidence-based approaches to offender detection and investigation continue to be a top priority for funders and policy makers. A systematic literature review was undertaken to address two related questions. First, what is the scale of the problem in the UK, in terms of the number of pedophilic and hebephilic individuals who pose a risk of contact offending against a child? Second, what is the potential socio-economic burden generated by the national IIOC suspect pool if left unattended to by targeted police action? Applying population estimates of pedophilia and hebephilia to the male population (16-89 years), we estimate there are between 2,365-5,991 males with paedophila and 12,218-30,952 males with hebephilia who are likely contact offenders. Applying average prevalence and incidence based costing methods to a conservative estimate of one victim per offender, the combined socio-economic burden from these persons could amount to £236-£597 million (incident costs) increasing to £2.9-£7.3 billion (lifetime costs; £3.3-£8.3 billion including QALY measures). Applying the same costs to CEOP’s (2013) estimate of 50,000 IIOC offenders we estimate that between 6000 and 27500 dual offenders could have already committed past contact offences, contributing an economic burden of between £97-£445 million (incident costs) increasing to £1.2-£5.4 billion (lifetime costs; £1.4-£6.2 billion including QALY measures). Future contact offences could contribute a further burden of £16-£18.6 million (incident costs) increasing to £198-£227 million (lifetime costs; £226-£260 million including QALY measures). Drawing upon these findings, we argue for the benefits of a research-informed prioritization approach to target IIOC offenders.